Beetle Preferences Callosobruchus Sp. On Some Types of Nuts - Muhammad Arif Wahyudin; Wiwin Windriyanti; Trijanti A. Widinni; Noni Rahmadhini (Future Science, 2023)
Legume agricultural products are among the Indonesian populace's primary sustenance sources. Nevertheless, the production of legumes in Indonesia needs to be improved, necessitating the country to engage in imports from several nations to meet demand. One of the factors contributing to this low production is the post-harvest seed deterioration that transpires during long-term storage. The grain beetle pest, Callosobruchus sp. (Coleoptera: Bruchidae), stands as one of the stored-product pests that exhibit a broad host range, encompassing various types of legumes. As a strategy to mitigate the resultant damages, it becomes imperative to examine the preference for egg-laying by Callosobruchus sp. on different legume species. Callosobruchus sp. egg-laying preference was assessed within the entomology laboratory of SEAMEO BIOTROP. This evaluation employed two distinct methodologies: the choice and no-choice tests, executed across various legume types. The selected legumes encompassed seven species: snap beans, mung beans, yardlong beans, peanuts, cowpeas, red beans, and soybeans. The testing outcomes unveiled that, under the choice test, Callosobruchus sp. laid the highest number of eggs on mung beans, totalling 70 eggs, followed by yardlong beans with 58 eggs. Subsequently, within the no-choice test, the highest egg deposition was observed on mung and yardlong beans, amounting to 87 eggs. Callosobruchus sp. preferred egg-laying and optimal development as imago on yardlong beans. Conversely, peanuts were the least favoured for egg-laying by Callosobruchus sp. and were deemed unsuitable for imago development. The attraction of Callosobruchus sp. is influenced by several factors, including seed essential constituents, seed texture, and microenvironmental conditions.